Nanopore sequencing reveals that DNA replication compartmentalisation dictates genome stability and instability in Trypanosoma brucei - Marija Krasiļņikova; Catarina A. Marques; Emma M. Briggs; Craig Lapsley; Graham Hamilton; Dario Beraldi; Kathryn Crouch; Richard McCulloch (Nature Communications)
Abstract The Trypanosoma brucei genome is structurally complex. Eleven megabase-sized chromosomes each comprise a transcribed core flanked by silent subtelomeres, housing thousands of Variant Surface Glycoprotein (VSG) genes. Additionally, hundreds of sub-megabase chromosomes contain 177 bp repeats of unknown function, and VSG transcription sites localise to many telomeres. DNA replication dynamics have only been described in the megabase chromosome cores, and in the single active VSG transcription site. Using a Nanopore genome assembly, we show that megabase chromosome subtelomeres display a paucity of replication initiation events relative to the core, correlating with increased instability. In addition, replication of the active VSG transcription site is shown to originate from the telomere, likely causing targeted VSG recombination. Lastly, we provide evidence that the 177 bp repeats act as conserved DNA replication origins, explaining submegabase chromosome stability. Compartmentalized DNA replication therefore explains how T. brucei balances stable genome transmission with localised instability driving immune evasion.